2020
DOI: 10.1016/j.chest.2020.03.055
|View full text |Cite
|
Sign up to set email alerts
|

Defining Extreme Phenotypes of OSA Across International Sleep Centers

Abstract: BACKGROUND: Extreme phenotypes of OSA have not been systematically defined. RESEARCH QUESTION: This study developed objective definitions of extreme phenotypes of OSA by using a multivariate approach. The utility of these definitions for identifying characteristics that confer predisposition toward or protection against OSA is shown in a new prospective sample. STUDY DESIGN AND METHODS: In a large international sample, race-specific liability scores were calculated from a weighted logistic regression that incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…40 Although age, sex, and BMI are traditional risk factors used toward OSA identification, some studies, including work from our group, have also observed that ethnicity/race and craniofacial features are potential predictive factors. 10,11,41,42 However, efficient identification of OSA remains problematic. Thus, there is a critical need for simple OSA prediction tools that could lead to widespread identification of the condition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…40 Although age, sex, and BMI are traditional risk factors used toward OSA identification, some studies, including work from our group, have also observed that ethnicity/race and craniofacial features are potential predictive factors. 10,11,41,42 However, efficient identification of OSA remains problematic. Thus, there is a critical need for simple OSA prediction tools that could lead to widespread identification of the condition.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were differences in the desaturation criteria, this large dataset (N ¼ 17,448) allowed for model development based on a generally uniform standard among all sites. 10,12,17 The incorporation of data from varying ethnicities also adds to the generalizability of the prediction models. In addition, the data used in these models represent readily available information from most clinical encounters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Obstructive sleep apnea (OSA) is a chronic condition caused by recurrent partial (hypopnea) or complete (apnea) upper-airway collapse during sleep and presents with a wide range of symptoms, including snoring and daytime sleepiness. 1,2 The estimated global prevalence of moderate to severe OSA amounts to over 425 million adults. [3][4][5] OSA leads to significant performance impairment, increased risk for accidents and elevated risk for metabolic and cardiovascular disease, depression, dementia, and stroke.…”
Section: Introductionmentioning
confidence: 99%